KEBIJAKAN BANK INDONESIA DALAM MEWUJUDKAN STABILITAS PEREKONOMIAN MELALUI PENGENDALIAN INFLASI DI KOTA DENPASAR - Ni Made Sumerti Asih; Putu Diah Putri Idawati (Forum Manajemen, 2020)
Bank Indonesia as the central Bank has an important role in the development of the country's economy in order to realize community Kesejahtraan. Otherwise if the state does not have a good economy then one of the inevitable impacts is inflation. Inflation is an economic illness that can be ignored because it can cause economic dissociation as well as slow economic growth and generate high unemployment, the purpose of this research is to know how Bank Indonesia's policy in realizing economic stability through inflation control the Dilaksankan Bank Indonesia policy is the 7-Day Repo Rate (BI-7DRR) which is a policy of interest rate by using 7-day time lag and Its multiplication. Other monetary policies: market opration policy, discount policy, cash reserve of selective credit policy, sanering, pulling and destroying old money as well as limiting the printing of new money. The results of the research show that Bank Indonesia has succeeded in realizing the economic stability in Denpasar through inflation control with the light inflation category below 10% per year.